2014
DOI: 10.1080/17550874.2014.980350
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on the climatic signal inAraucaria araucanafrom xeric sites in Patagonia, Argentina

Abstract: Background: At different cambial ages, trees experience changes in their structure and interactions with environmental conditions. Reciprocal mechanisms between tree age and physical resources, photosynthetic rates, and xylem production may influence hydraulic resistance and plant water stress. However, it is yet uncertain how these mechanisms are associated with changes in growth sensitivity to biophysical drivers, especially climate. Aim: To establish age-associated climate -growth relationships in growth ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Additionally, several recent studies based on tree rings have demonstrated that the response to climate varies with stand age (e.g., Esper et al, 2008;Yu et al, 2008;Rozas et al, 2009;Vieira et al, 2009;Wang et al, 2009;Copenheaver et al, 2011;Hadad et al, 2015). However, Colenutt and Luckman (1991) have suggested that in some cases this duality has not been proven; for example, they found no difference in the response of both young and older Larix lyallii trees to climate.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Additionally, several recent studies based on tree rings have demonstrated that the response to climate varies with stand age (e.g., Esper et al, 2008;Yu et al, 2008;Rozas et al, 2009;Vieira et al, 2009;Wang et al, 2009;Copenheaver et al, 2011;Hadad et al, 2015). However, Colenutt and Luckman (1991) have suggested that in some cases this duality has not been proven; for example, they found no difference in the response of both young and older Larix lyallii trees to climate.…”
Section: Introductionmentioning
confidence: 86%
“…While some authors argue that stand age affects the signals of climate that can be observed in plants (e.g., Szeicz and MacDonald, 1994;Carrer and Urbinati, 2004;Linderholm and Linderholm, 2004;Esper et al, 2008;Rozas et al, 2009;Vieira et al, 2009;Hadad et al, 2015), other studies show that climate growth responses are age independent (e.g., Fritts, 1976; Linares et al, 2013;Sun and Liu, 2014). The present study shows that P. cooperi trees from the Sierra Madre Occidental in northern Mexico that are younger than 80 years are more sensitive to the influence of climate than older trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ring width was considered as the response variable, sex of individuals as the fixed factor, and sites and stands within sites as random factors. As variables we used those months of precipitation and temperature with the stronger and significant relationship with growth Hadad et al, 2015). The months of precipitation were January of the prior growing period and September of the current period of growth.…”
Section: Ring Width Data Analysesmentioning
confidence: 99%
“…The pehuén is known to be an old tree, reaching ages surpassing 900 years, particularly in forest patches placed on rocky outcrops and surrounded by the dry Patagonian steppe (LaMarche et al, 1979;Hadad et al, 2015). As indicated by previous reports, the inter-annual variability in the ring widths of A. araucana trees reveal a strong dependence to the spring-summer climate conditions during both current and prior period of growth (Villalba et al, 1989;Mundo et al, 2012;Muñoz et al, 2013;Hadad et al, 2015) and at scales of climate forcing it has been observed that growth is lower the higher the spring-summer value of the Southern Annular index Hadad et al, 2015). Moreover, another factor that may have an impact on growth is the incidence of seed production.…”
Section: Introductionmentioning
confidence: 99%